107k views
0 votes
What is -5-(15y-1)=2(7y-16)-y

2 Answers

1 vote
the answer should be y=1
User Charlie Frater
by
5.3k points
5 votes

Answer:

y = 1

Explanation:

- 5 -(15y - 1) = 2(7y - 16) - y

1. Distribute

- 5 - 1(15y - 1) = 2(7y - 16) - y

- 5 - 15y + 1 = 14y - 32 - y

2. Add Like Terms

- 5 - 15y + 1 = 14y - 32 - y

- 5 - 15y + 1 = 14y - 33

- 5 - 15y + 1 = 14y - 33

- 4 - 15y = 14y - 33

3. Addition prop. of eq.

(- 4 + 4) - 15y = 14y (- 33 + 4)

- 15y = 14y - 29

4. Subtraction prop. of eq.

(- 15y - - 14y) = (14y - 14y) - 29

-29y = -29

5. Division prop. of eq.

(-29y/-29y) = (-29/-29)

y = 1

User RufusInZen
by
5.0k points